Avaliação da atividade gastroprotetora de Maytenus distichophylla Mart. ex Reissek (Celastraceae) - Caldas Filho, Marcelo Ricardo Dutra (2013)
Maytenus distichophylla Mart. ex Reissek, popularly known as "casca amarela" or "pau-colher", belongs to the family Celastraceae. This species was selected for this work from chemotaxonomic criteria, with a view that has been proven to gastroprotective activity in several species of this genus, which was attributed to secondary metabolites such as flavonoids, terpenoids, alkaloids and tannins. Aiming to assess the acute toxicity, gastroprotective activity, as well as mechanisms related to this activity were obtained, from the leaves of M. distichophylla, crude methanolic extract (Md-MeOHE) and ethyl acetate phase (Md-EtOAcP). The single administration (p.o.) of 2000 mg/kg in mice Md-MeOHE, did not cause behavioral changes in the evaluated parameters (such as hyperactivity, piloerection, analgesia, ambulation, among others), also caused no changes in weight or the gross structure of organs. However, was able to reduce the consumption of water and feed in male animals. Unable to determine the LD50, whereas no deaths at the end of 14 days of observation. Regarding the gastroprotective activity, Md-MeOHE and Md-EtOAcP at doses of 62.5, 125, 250 and 500 mg/kg (p.o.) were tested against different models of acute induction of ulcer (ethanol acidified, ethanol, stress immobilization and cold, nonsteroidal anti-inflammatory drug (NSAID) and containment of gastric juice). In the model of acidified ethanol, the Md-MeOHE reduced the ulcerative lesion index (ULI) for 68, 84, 81 and 80%, respectively. Front lesions by ethanol, Md-MeOHE and Md-EtOAcP in the same doses protected the gastric mucosa 40, 56, 65, 86, 12, 34, 46 and 71%, respectively. When assessing the model stress- Md-MeOHE and Md-EtOAcP decreased ULI at 58, 72, 79, 84, 29, 38, 50 and 52%, respectively. Likewise, in the model of NSAID-induced gastric ulcers, lesions was no inhibition at 46, 65, 81 and 82% for Md-MeOHE and 26, 40, 58 and 69% for Md-EtOAcP. In the ulcers induced by restraint of gastric juice (pylorus ligature) the Md-MeOHE and Md-EtOAcP in its most effective doses (500 mg/kg) caused gastric mucosa protection when administered intraduodenally 75 and 77%, respectively, compared to negative control. Also on ligation model (i.d.), Md-MeOHE and Md-EtOAcP reduced the volume of gastric contents. In order to investigate the mechanisms of action related to gastroprotection promoted by Md-MeOHE (500 mg/kg) and Md-EtOAcP (500 mg/kg), was evaluated the involvement of sulfhydryl groups, nitric oxide, prostaglandins and mucus. Thus, it was verified that the gastroprotective effect of plant samples of M. distichophylla not involve increased mucus adhered to the mucosa or participation of nitric oxide. However, this effect is related to the participation of sulfhydryl groups and increased levels of prostaglandin. Thus, these data suggest that M. distichophylla presents gastroprotective activity, possibly related to mechanisms antisecretory and cytoprotective.